2014
DOI: 10.1111/srt.12132
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent changes in stratum corneum barrier function

Abstract: Skin aging, body site and environmental exposure can affect the SC barrier function, its structure, and its lipid content. The thickening of the SC with age compensates for the decrease of the quantity and ordering of the lipidic cement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
98
4
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(133 citation statements)
references
References 34 publications
(40 reference statements)
16
98
4
3
Order By: Relevance
“…The reason(s) for the reduced barrier function in the upper inner arm are unclear, but could include structural factors relating to overall growth, such as overall skin thickness including non-SC layers (not measured in these studies), biological factors such as lipid distribution within the different skin locations, changes in NMF production and a greater environmental exposure of the dorsal forearm than the upper inner arm. In adults, resistance to water permeability was shown to be greater for the upper inner arm than the dorsal forearm, with no significant difference in TEWL between sites [10,20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason(s) for the reduced barrier function in the upper inner arm are unclear, but could include structural factors relating to overall growth, such as overall skin thickness including non-SC layers (not measured in these studies), biological factors such as lipid distribution within the different skin locations, changes in NMF production and a greater environmental exposure of the dorsal forearm than the upper inner arm. In adults, resistance to water permeability was shown to be greater for the upper inner arm than the dorsal forearm, with no significant difference in TEWL between sites [10,20]. …”
Section: Discussionmentioning
confidence: 99%
“…TEWL varies by body site within subjects and can be variable within similar subject populations [7,10,19,20]. There have been differing trends of TEWL with age reported in the literature [9,12,21].…”
Section: Introductionmentioning
confidence: 99%
“…Niacinamide, a compound of vitamin B 3 which has been shown to increase the levels of SC ceramides [35], was also tested on healthy skin, resulting in a lower increase of TEWL following tape stripping [36]. On the other hand, a study by Boireau-Adamezyk et al [37] showed that the relationship between lipids and TEWL is not straightforward in the facial area, characterized by higher levels of ceramides, cholesterol and the lipid/protein ratio, as well as hydration, and yet by a poor barrier function indicated by high TEWL. Smaller, immature corneocytes and thinner SC, driven by faster proliferation, have also been reported in the literature for facial skin [38,39]; these factors, leading to a shorter diffusion path length through the corneocytes [40], most probably play a major role in the increase of TEWL.…”
Section: Resultsmentioning
confidence: 99%
“…TEWL is a clinically relevant test used to measure skin barrier function [21]. When high and low stress areas of measurement were taken together (Figure 2(a)) or when they were considered separately (Figure 2(b) and (c)), there was no difference in SoC and EVS socket TEWL values at the baseline time point.…”
Section: Elevated Vacuum Suspension Preserved Skin Barrier Functionmentioning
confidence: 99%